Trump Policy 2.0: Implications For Fiscal And Monetary Stability And The Resilience Of The Islamic Financial Sector In Indonesia - Faris Kurnia Hakim; Mauizhotul Hasanah; Safarinda Imani; M. Taufiq (DPPM Universitas Pelita Bangsa, 2026)
The protectionist policies implemented by the United States under Donald Trump, particularly through impor tariffs on trading partners, including Indonesia, have created uncertainty in global trade. These tariff increases will disrupt the economic stability of partner countries, including Indonesia. The impact can be reflected in fiscal stability, monetary stability, and the resilience of the financial sector, particularly Islamic finance. Therefore, this study aims to analyze how US tariff policy impacts these three pillars of economic stability using VAR and VECM methods. Data used ranges from 2016 to 2025. Overall, the VAR model estimation results indicate that all variables have a long-term relationship. Therefore, the VECM model, measured by the error correction term (ECT), estimates the impact of Trump's import tariffs on fiscal, monetary, and Islamic financial stability indicators. The variables with significant effects are state budget deficit, government debt, rupiah exchange rate, foreign exchange reserves, Indonesia Sharia Stock Index (ISSI), and Financing to Deposit Ratio (FDR). Meanwhile, the variables with insignificant effects are state revenue, inflation, and Non Performing Financing (NPF). Furthermore, in the short term, the variables with significant effects are all fiscal stability variables (state revenue, state budget deficit, government debt), and Islamic financial stability (ISSI and FDR). The variables with insignificant effects are monetary stability variables (rupiah exchange rate, inflation, foreign exchange reserves) and Islamic financial stability (NPF).